2012
DOI: 10.1103/physrevb.85.174434
|View full text |Cite
|
Sign up to set email alerts
|

Layered antiferromagnetic spin structures of expanded face-centered-tetragonal Mn(001) as an origin of exchange bias coupling to the magnetic Co layer

Abstract: Spin structures of an exchange-coupled-bilayer system of expanded-face-centered-tetragonal (e-fct) Mn(001) ultrathin films grown on Co/Cu(001) were resolved by means of spin-polarized scanning-tunneling microscopy. With an in-plane spin-sensitive probe, a layered antiferromagnetic-spin ordering of Mn overlayers was evidenced directly. In addition, the spin frustration across the same Mn layer creating a narrow domain wall down to nanometer scale was also observed along the buried step of Co underlayers. Accord… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…As mentioned in the previous section, the results obtained in the current study support an in-plane layered AFM structure for the fcc-like Mn thin films grown on in-plane magnetic FM films (or vice versa) [10,23,24,29]. In the case of the fcc-Mn thin film, a previous XMCD-PEEM study on in-plane magnetic Fe/fcc-Mn/Cu 3 Au(001) reported the presence of uncompensated magnetic moments in the Mn layer [10]; this study also observed the presence of an uncompensatedcompensated transition of the Mn magnetic interface along with the continuous variation of t Mn .…”
Section: B Correlation Of Afm Structure and Uncompensated Mn Momentssupporting
confidence: 88%
See 2 more Smart Citations
“…As mentioned in the previous section, the results obtained in the current study support an in-plane layered AFM structure for the fcc-like Mn thin films grown on in-plane magnetic FM films (or vice versa) [10,23,24,29]. In the case of the fcc-Mn thin film, a previous XMCD-PEEM study on in-plane magnetic Fe/fcc-Mn/Cu 3 Au(001) reported the presence of uncompensated magnetic moments in the Mn layer [10]; this study also observed the presence of an uncompensatedcompensated transition of the Mn magnetic interface along with the continuous variation of t Mn .…”
Section: B Correlation Of Afm Structure and Uncompensated Mn Momentssupporting
confidence: 88%
“…This could substantially reduce the domain size of the adjacent FM layer because of the established collinear coupling and biquadratic coupling. Because the experimental results obtained in previous studies have indicated a layered-AFM structure of Mn films in fcc-like Mn/FM bilayers [10,29], in the current study, the strength of the long-range lateral exchange coupling between fcc-Mn and fct-Mn films can be distinguished by monitoring the features of the AFM-induced domain evolution.…”
Section: A Long-range Afm Ordering Probed By Magnetic Domain Imagingmentioning
confidence: 87%
See 1 more Smart Citation
“…In an independent study, Yamada et al repeated the same measurement on a system with Mn on top of Fe(001), but found the domain-wall width to be nearly independent of the Mn thickness [19]. Similar frustrated spin configurations have also been reported in other systems [8,9,[20][21][22][23][24][25][26][27][28][29][30]. The frustration induced domain wall in nanorings is considered to lead to potential logic and memory applications [31].…”
Section: Introductionmentioning
confidence: 71%
“…Indeed, surface defects of this type are practically unavoidable. Their presence at magnetically active interfaces often leads to nonnegligible magnetic frustration, resulting in complex spin textures [1][2][3][4][5][6][7][8][9]. This is especially true for most of the cases of practical relevance, where the exchange coupling across the AFM/FM interface is quite strong and is of primary importance for the understanding and design of various front-edge applications, such as magnetic storage, magnetic sensors, etc [10][11][12].…”
Section: Introductionmentioning
confidence: 99%